A universal spray printing strategy to prepare gradient hybrid architectures. Issue 4 (21st March 2022) - Du, Lingyu; Bi, Songshan; Hu, Yang; Wang, Rui; Zhu, Jiacai; Zhang, Minghui; Niu, Zhiqiang
Abstract: Functionally gradient materials (FGMs) have attracted tremendous attention due to their unique properties and structures. However, it is still a great challenge to prepare scalable FGMs by a universal, cost‐effective, and highly efficient method. Here, a strategy of combining in situ concentration regulation and spraying is developed to fabricate continuously gradient composite films (GCFs), where the component gradient variation can be well controlled. This strategy is universal and versatile, which is beneficial to inducing different components into GCFs with gradient distributions and further constructing them with diverse configurations on various substrates. The gradient design endows the composite films with excellent mechanical strength and gradient electron transport pathways, which ensures that GCFs directly serve as the electrodes in electrochemical devices. As a proof of concept, free‐standing GCFs based on V2 O5 nanomaterials are used as cathodes of aqueous zinc‐ion batteries. The resultant devices deliver superior electrochemical performances in comparison with the counterparts of homogeneous case. Therefore, this universal strategy provides a promising route in the scalable production of FGMs and further extends their applications in various fields. Abstract : A universal and versatile strategy of combining in situ concentration regulation and spraying is developed to fabricate continuously gradient composite films, where the component gradient distributions are controllable and diverse configurations can be readily designed on various substrates. The gradient structure endows composite films with excellent mechanical strength and unique electron conduction pathways, which extends their application in energy storage devices.